A cross-cultural study of psychological well-being among British and Malaysian fire fighters - Mohd. Dahlan A. Malek; Ida Shafinaz Mohamed Kamil (2016)
Psychological consideration has always been a part of society and it usually relates to values, beliefs, ethnicity and gender. This is the essence of cultural psychology. In recent times, this branch of psychology has developed the new arm of Cross-Cultural Psychology, an extension of psychology covering the influence on behaviour when cultural groups interact. This study is a comparative study of two cultural groups, namely Malaysian and British fire fighters. Sources of occupational stress and their impact on psychological wellbeing were examined in a questionnaire survey of 1053 British and Malaysian fire fighters. The role of coping strategies as moderating factors was also tested. Sources of occupational stress had significant negative correlations with psychological wellbeing. Hierarchical regression analysis was used to examine the moderating effect of coping strategies on psychological wellbeing and found differences between the British and Malaysian fire fighters. Models of psychological wellbeing for both cultures were produced.